A cross-sectional study: caregiver burden and related determinants of adult patients with β-thalassemia major in mainland China - Runqi Zhang; Shuo Zhang; Jing Ming; Jing Xie; Baoguo Liu; Weihang Jiang; Yingjie Fu; Xuemei Zhen; Xiaojie Sun (BMC, 2024)
Abstract Background The informal caregivers of adult patients with β-thalassemia major (β-TM) bear not only physical but also emotional and economic pressures of providing care. This study is the first to evaluate the caregiver burden by Zarit Burden Interview (ZBI) of adult patients with β-TM in mainland China and to identify predictors of caregiver burden. Methods In this cross-sectional study, we conducted an online survey with snowball sampling covering seven provinces between September 1, 2021, and January 31, 2022, of patients aged ≥ 18 years with β-TM and their informal caregivers. Caregiver burden was assessed using the ZBI. Data on patient demographics, disease and therapy characteristics, and informal caregivers' demographic characteristics were collected and analysed using independent t-tests, analysis of variance, Spearman's correlation and multiple linear regression. Results Of 75 included patients, more than half (50.7%) were male. The mean patient age was 24.69 ± 5.59 years. The mean age of the informal caregivers was 50.60 ± 9.16 years, with women (74.7%) being predominant. The ZBI score was 38.00 ± 17.02. Multiple linear regression analysis showed that patients with interrupted blood transfusion therapy and informal caregivers required to care of others were positively associated with caregiver burden (p < 0.05). Age of informal caregivers were borderline significant positively associated with caregiver burden (p < 0.1). Married informal caregivers were negatively associated with caregiver burden (p < 0.05). Conclusions The informal caregivers of adult patients with β-TM in mainland China experienced a moderate-to-severe level of caregiving burden. The caregiver burden was higher in patients with a history of interrupted blood transfusion therapy or in informal caregivers who were older or needed to care for others. Additionally, married informal caregivers experienced lower burdens compared to non-married informal caregivers. These findings provide a reference to identify informal caregivers with higher burdens among patients with β-TM.